Clinical and morphological parallels in the diagnosis of squamous cell carcinoma of the breast: a description of a clinical case - Ye. Ye. Palkina; Ye. N. Allenova (Опухоли женской репродуктивной системы, 2014)
Squamous cell carcinoma of the breast is a very rare form of metaplastic cancer and usually occurs in the elderly. A macroscopically tumor nodule frequently contains cystic cavities, by determining the size of a tumor. The local extent of the tumor in the absence of regional metas- tases characterizes a relatively favorable course.